Pengaruh Kualitas Pelayanan, Produk Dan Harga Terhadap Kepuasan Konsumen Pada Bolu Kuwuk Dusun Kawang Banyuwangi - Muhaimin, Moh Ali; Wahono, Budi; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This research aims to test and explain the influence of service quality, product and price on consumer satisfaction in Bolu Kuwuk, Kawang Banyuwangi hamlet. The sample used in this research was 100 respondents using the Malhotra method with a proportional sampling technique. It is a quantitative data analysis method using multiple linear regression analysis. The data used is partial hypothesis testing (t test). The results of this research show that partially (t test) the variables of service quality, product and price influence consumer satisfaction at Bolu Kuwuk, Kawang Banyuwangi village. Â Keywords: Service and Product Quality, Price, Satisfaction.